Sandifer's syndrome: Investigations and treatment - Gordon, Neil S. (Journal of Pediatric Neurology, 2007)
The symptoms and signs of Sandifer's syndrome are described, especially the abnormal movements, which can wrongly be diagnosed as some form of dystonia. They affect head, neck and chest, and are often accompanied by abnormal postures. The syndrome, may or may not, be associated with hiatus hernia, and gastro-intestinal symptoms are common. Neurologically impaired children are especially at risk, and can present particular difficulties in diagnosis. Barium swallow can confirm the diagnosis, and also help to establish the cause. The possible reasons for the syndrome are considered, relief of abdominal discomfort being most plausible. Treatment can result in dramatic improvement, although sometimes surgery is needed.
Keywords: Sandifer's syndrome; symptoms; investigations; treatment